Pengembangan Sistem Manajemen Bimbingan Skripsi (Studi Kasus: Fakultas Ilmu Komputer Universitas Brawijaya) - Muhammad Kevin Andhiya Rizky; Achmad Arwan; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
At the University level, undergraduate students are required to prepare a final project or thesis as a condition for obtaining a bachelor's degree. Thesis is a term used by universities throughout Indonesia which describes a scientific paper which includes an explanation of the research results conducted by undergraduate students (S1) to study a phenomenon or problem that exists in the relevant field of science using the rules applies to related agencies. In the thesis activity at the Faculty of Computer Science, Brawijaya University, students are guided by two mentors. In thesis guidance activities that involve several actors and agendas, it causes the thesis guidance activities to be managed properly. To realize this, an application is needed that can support the thesis guidance management process. This web-based application development aims to facilitate thesis guidance activities. This application that can be used by students and supervisors has main features such as lecturer submissions, thesis guidance scheduling, and guidance logbooks that can make thesis activities more structured and organized. This web-based application has gone through the unit testing phase, integration testing and validation testing. The results of these tests produce a valid value of 100%.